Effect of Escherichia coli heat-stable enterotoxin, cholera toxin and theophylline on ion transport in porcine colon - Argenzio, R. A. (1981)
1. The effect of heat-stable enterotoxin (ST) of Escherichia coli, cholera toxin (CT), and theophylline (a phosphodiesterase inhibitor) on ion and water transport was studied with an in vivo isolated loop system of the pig colon. 2. All three agents abolished net Na absorption as a result of a decrease in the lumen to blood Na flux alone. With all three agents, net Cl absorption was reduced, but not abolished, and net HCO(3) secretion was elicited. Luminal p(CO(2)) was reduced with CT and theophylline from that observed in normal Ringer alone. 3. Theophylline resulted in a prompt and sustained increase in both cyclic adenosine monophosphate (cyclic AMP) and cyclic guanosine monophosphate (cyclic GMP) levels in colonic mucosa studied in vitro. ST selectively elevated cyclic GMP, whereas CT selectively elevated cyclic AMP. These responses paralleled the time course and magnitude of response of the transepithelial electrical potential difference (ψ(LB)) measured in vivo. 4. Ion replacement studies in the presence or absence of theophylline showed that in the absence of Na, Cl absorption was slightly reduced and HCO(3) secretion was elicited; no further additive effects of theophylline in the absence of luminal Na were observed. In the absence of luminal Cl, net Na absorption was abolished and HCO(3) was absorbed; theophylline resulted in significant net Na and HCO(3) secretion. Theophylline also increased ψ(LB) in the absence of either luminal Na or Cl. 5. Results suggest that in the presence of theophylline or enterotoxin, the coupled Na—H and Cl—HCO(3) exchange processes that are normally responsible for at least half of the net NaCl absorption by this tissue are interrupted. Active HCO(3) secretion is observed and Cl absorption under these conditions can be entirely explained as a consequence of ψ(LB). Thus, these studies indicate that the colon may participate in the production of diarrhoea of enterotoxigenic origin. They also suggest an important functional role of cyclic nucleotides in controlling the acidity and volume of colonic contents.